2022
DOI: 10.1038/s41598-022-13442-4
|View full text |Cite
|
Sign up to set email alerts
|

Designing of multi-epitope chimeric vaccine using immunoinformatic platform by targeting oncogenic strain HPV 16 and 18 against cervical cancer

Abstract: Cervical cancer is the most common gynaecological cancer and reaches an alarming stage. HPVs are considered the main causative agents for cervical cancer and other sexually transmitted infections across the globe. Currently, three prophylactic vaccines are available against HPV infections with no therapeutic values. Due to a lack of effective therapeutic and prophylactic measures, the HPV infection is spreading in an uncontrolled manner. Next-generation of vaccine is needed to have both prophylactic and therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Alpha helix and coilcontaining proteins and peptides are significant structural antigens because antibodies can identify them. 24 The amino acid composition has shown that leucine residues are the most frequently occurring amino acids in all three proteins, i.e., E6, E7, and L1 of HPV-45. The most intriguing fact is that leucine residues have been studied earlier due to their significance in histone deacetylases (HDACs) binding.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha helix and coilcontaining proteins and peptides are significant structural antigens because antibodies can identify them. 24 The amino acid composition has shown that leucine residues are the most frequently occurring amino acids in all three proteins, i.e., E6, E7, and L1 of HPV-45. The most intriguing fact is that leucine residues have been studied earlier due to their significance in histone deacetylases (HDACs) binding.…”
Section: Discussionmentioning
confidence: 99%
“…The PSIPRED results reveal that the vaccine construct possessed 19.7% alpha-helix, 16.9% extended strands and 63.4% coils. It is to be noted that proteins having an alpha-helix and coils are important as structural antigens for they can be recognised by antibodies [54]. The 3D structure of the final vaccine construct was predicted using the ROBETTA sever, and model 2 was chosen based on the model evaluation using the SAVES server.…”
Section: Prediction and Assessment Of Secondary And 3d Structure Of T...mentioning
confidence: 99%
“…Another vaccine for the treatment of cervical cancer was designed with epitopes of HPV16/18 E5 and E7 proteins and showed stability, non-toxicity, and non-allergenicity [ 38 ]. Kumar et al [ 39 ] went further, designing a multi-epitope platform with prophylactic and therapeutic potential against HPV16 and 18 from peptides obtained from L1, E5, E6, and E7 proteins that can induce an immune response against CD8+ and TCD4+ lymphocytes.…”
Section: Strategies To Improve the Efficiency Of Nucleic Acid Vaccinesmentioning
confidence: 99%